SURVEI SARANA DAN PRASARANA OLAHRAGA PENUNJANG PROSES PEMBELAJARAN PENJASORKES DAN PEMANFAATANNYA DI SEKOLAH LUAR BIASA KABUPATEN TEMANGGUNG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
These results indicate that the availability of sports facilities and infrastructure in SLB Temang- in 2013 is the game ball (94%) unfavorable category, the small ball game equipment (114%) category very well, gymnastic equipment (110%) the category of very good, athletic equipment (102%) very good category, physical fitness exercise equipment (100%) either category, outdoor activity equipment (174%) very good category. While the average for the availability of sports infrastructure in the State Disability Waterford School is an excellent 115% category. The results of its use, the ball of the equipment used (84.5%) either category, small appliances balls (83%) either category, gymnastic equipment (85%) categorized as good, athletic equipment (70.5%) either category, and fittings fitness physical exercise (75%) either category, and the average utilization of the facilities and infrastructure (80%) both in the use of sports categories first semester. From the results it can be concluded that the emphasis on the availability of facilities and infrastructure that support the school Penjasorkes exceptional utilization has been very good and has been good enough to learn the sport.